MILITARY AND GEOGRAPHIC MODELING OF TERRITORY DEVELOPMENT BASED ON THE CELLULAR AUTOMATA METHOD - Mikhno, O.; Patrakeyev, J.; Levinskova, N. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
Prognostic modeling of urbanized territory should be an integral component of military and geographical analysis of operational-strategic direction. In the absence of sufficient information from various means of intelligence, forecasts, including long-term ones, can significantly increase the reliability of information in the decision-making support system. Based on this, the methods of mathematical-cartographic modeling have the right to exist in such system as an additional source of prognostic information. From all variety of methods of mathematical-cartographic modeling, the method of cellular automata was chosen for study, as a discrete in time, dynamic in space and multifactorial process. Thorough analysis of literary sources, which determine the state and modern trends in development of cartographic modeling of territorial development of cities in the world, was carried out. The place of the method of cellular automata in the system of mathematical- cartographic modeling as tool for creating prognostic models of dynamics of spatial distribution of phenomena is determined. The structure of spatial database of mathematical-cartographic modeling of the territorial development of Ukrainian city Dnipro has been developed. Local transition functions are constructed that determine the relationships between single cellular automata in the raster surface of simulation. A software application was developed in high-level Python general-purpose programming language, integrated into the environment of ArcGIS geoinformation system, and modeling of territorial development of city Dnipro was carried out. As a result of modeling, scenarios of the city's development for the next five and ten years were obtained. The growth of the area of territorial development of city Dnipro in the next five years may amount to seventy-two square kilometers, and in the next ten years – one hundred and twelve square kilometers. In total, the expansion of the city territory by one hundred and eighty-four square kilometers is predicted, which will ensure its total increase by forty-four percent.
Keywords: military-geographical analysis, mathematical-cartographic modeling, cellular automata method, urban environment